Clinical characteristics and oncological outcomes in negative multiparametric MRI patients undergoing robot‐assisted radical prostatectomy. Issue 11 (31st May 2021) - Wagaskar, Vinayak G.; Ratnani, Parita; Levy, Micah; Moody, Kate; Garcia, Mariely; Pedraza, Adriana M.; Parekh, Sneha; Pandav, Krunal; Shukla, Bhavya; Sobotka, Stanislaw; Haines, Kenneth; Wiklund, Peter; et al.
Abstract: Background: Efforts are ongoing to try and find ways to reduce the number of unnecessary prostate biopsies without missing clinically significant prostate cancers (csPCa). The utility of multiparametric magnetic resonance imaging (mpMRI) in detecting prostate cancer (PCa) shows promise to be used as triage test for systematic prostate biopsy. Our aim is to Study clinical parameters and oncological outcomes in men with negative mpMRI (nMRI; PI‐RADS v2 scores of ≤ 2) who underwent robot‐assisted radical prostatectomy (RARP) to evaluate nMRI's practicality as a biopsy triage test. Methods: Retrospective analysis of 331 men with nMRI who underwent RARP between 2014 and 2020 compared with men with positive mpMRI (pMRI; PI‐RADS v2 scores ≥ 3, N = 1770). csPCa was defined as Gleason score ≥ 3 + 4 and biochemical recurrence (BCR) was defined as PSA > 0.2 ng/ml on two occasions. Biopsies were graded with the International Society of Urologic Pathology [ISUP] grade. Descriptive statistics for nMRI and pMRI were performed. Mann–Whitney U test was used for continuous variables and χ 2 for categorical variables. Univariable and multivariable regression analyses were performed. Results: Univariable analysis shows statistically significant difference ( p < .05) between median age (nMRI‐61 years vs. pMRI 63 years), race (higher incidence of nMRI in African American men), use of 5‐alpha reductase inhibitors (higher rate in nMRI). While incidence rates of family history of PCa, suspicious digital rectal examination (DRE) findings, median PSA levels and 4Kscore, were lower in nMRI versus pMRI. Rates of positive surgical margins and BCR were comparable in nMRI versus pMRI. Biopsy ISUP Grades I and II upgraded by 51% and 12%, respectively in final pathology. African American race and no history of the prior negative biopsy were significant predictors for upgrading. Conclusion: Men with nMRI pose diagnostic challenges as they tend to be younger patients with lower rates of suspicious DRE findings and lower 4K scores, yet comparable oncological outcomes in csPCa rates, positive surgical margins, and BCR rates.